2016
DOI: 10.7196/samj.2016.v106.i12.12005
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and modifiable predictors of blood pressure control for hypertension in primary care attenders in the Western Cape, South Africa

Abstract: Background. Low socioeconomic status is associated with the risk of hypertension. There are few reports of the effect of socioeconomic and potentially modifiable factors on the control of hypertension in South Africa (SA). Objectives. To investigate associations between patients' socio economic status and characteristics of primary healthcare facilities, and control and treatment of blood pressure in hypertensive patients. Methods. We enrolled hypertensive patients attending 38 public sector primary care clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Recent studies show a high prevalence of dysglycaemia, dyslipidaemia and increased visceral adiposity in HIV‐infected patients on ART, thereby predisposing to hypertension and diabetes . While efforts to maintain progress with ART must continue, our findings point to a need to expand our focus to enable effective management of communicable disease and NCD comorbidity particularly among lower socioeconomic groups .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent studies show a high prevalence of dysglycaemia, dyslipidaemia and increased visceral adiposity in HIV‐infected patients on ART, thereby predisposing to hypertension and diabetes . While efforts to maintain progress with ART must continue, our findings point to a need to expand our focus to enable effective management of communicable disease and NCD comorbidity particularly among lower socioeconomic groups .…”
Section: Discussionmentioning
confidence: 86%
“…The burden of non‐communicable diseases (NCDs), including hypertension and type 2 diabetes mellitus, is increasing alongside established HIV and tuberculosis epidemics among people in sub‐Saharan Africa . This is fuelled by increasing urbanisation, changing diet, sedentary lifestyles and, among people with HIV, possibly by metabolic side effects of lifelong antiretroviral treatment . WHO has predicted a 17% increase in global NCD deaths from 2013 to 2020, with low‐ and middle‐income countries (LMICs) currently already bearing 86% of the burden of these premature deaths .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, studies carried out in several countries around the world, both developed and developing, show the existence of socioeconomic inequalities in various aspects of health. It is observed that the socioeconomically disadvantaged population is generally the one with the lowest levels of health [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Democratic Republic of Congo, there were no significant differences in BP outcomes between general referral hospitals and community health centers [56]. Additionally, the presence of the doctor on a daily basis (OR:1.64; 95% CI:1.17-2.31; p =0.004) and a higher mean number of nurses in the clinic (OR: 1.15; 95% CI:1.08-1.23; p =0.001) were significantly associated with BP control at the baseline of a randomized controlled trial conducted in South Africa [71].…”
Section: Resultsmentioning
confidence: 99%